2020
DOI: 10.1111/tmi.13502
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors of drug‐resistant tuberculosis in Thailand: results from the fifth national anti‐tuberculosis drug resistance survey

Abstract: objective To assess the prevalence and risk factors of drug-resistant tuberculosis (TB), the fifth national anti-TB drug resistance survey was conducted in Thailand. methods A cross-sectional study was conducted by stratified cluster sampling with probability proportional to size of TB cases from public health facilities in 100 clusters throughout Thailand from August 2017 to August 2018. Susceptibility testing of TB isolates to first-and second-line anti-TB drugs was performed on Löwenstein-Jensen medium usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 12 publications
0
8
2
1
Order By: Relevance
“…The prevalence of Hr-TB in Thai adults has remained stable since 2006, at approximately 10% ( Kamolwat et al., 2021 ). Our study reported that the prevalence of Hr-TB in Thai children was 10.8% — comparable with previous studies in Thailand (11.5% in 2001–2010 and 13% in 2008–2011) ( Lapphra et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Hr-TB in Thai adults has remained stable since 2006, at approximately 10% ( Kamolwat et al., 2021 ). Our study reported that the prevalence of Hr-TB in Thai children was 10.8% — comparable with previous studies in Thailand (11.5% in 2001–2010 and 13% in 2008–2011) ( Lapphra et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study also points to an important aggravating factor, which is the growing trend of cases of resistance to drugs used in the treatment of TB. This reality is also present in other countries of the world, which introduces the concern that treatment has not been effective, in addition to the possibility of transmission in its resistant form [ 4 , 5 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even in the face of this recommendation, active TB cases remain within penal establishments, a factor that demonstrates how serious the scenario experienced by inmates is. The lack of early diagnosis and a correct health surveillance system in the penitentiary contributes to the development of resistance to drugs used for the treatment of TB [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…to research from Africa, China, and Thailand, being over 45 years old is associated with a lower treatment success rate. [42][43][44] Older age was associated with higher comorbidity with increased pill burden and adverse events and poor treatment adherence. This age group is also predisposed to interact with MDR-TB patients, and has a higher risk of smoking, alcoholism, loss of follow-up, and other social factors that contribute to the development of resistant TB.…”
Section: Strength and Limitationsmentioning
confidence: 99%